2000
DOI: 10.1007/s004020050459
|View full text |Cite
|
Sign up to set email alerts
|

Rotational profile of the lower extremity and foot progression angle: computerized tomographic examination of 50 male adults

Abstract: Acetabular, femoral and tibial torsion of 50 normal adult male subjects were measured by computerized tomography and the relationship between these angles and foot-progression angle was examined. The mean acetabular anteversion was 15.6 degrees on the right and 15.8 degrees on the left, (range 3 degrees-30 degrees). The mean femoral torsion was 6.5 degrees on the right and 5.8 degrees on the left (range 14 degrees-28 degrees). The mean tibiofibular torsion was 30.9 degrees on the right and 29.1 degrees on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 16 publications
7
36
1
Order By: Relevance
“…13,48,79 Our mean hip anteversion values are within the range of normal values reported in healthy adults (7°-18°), as measured by both clinical and diagnostic methods. 8,36,63,65,71,72 Our findings of greater hip anteversion in females as compared to males agree with those of other studies 8,63 ; but the magnitude of the sex difference is much larger in the current study (approximately 9° versus 2°-4°). This disparity may be explained by differences in measurement methods, as the previous studies report measures on cadavers or with ultrasound and the current study used clinical measures in healthy subjects.…”
Section: Hip Anteversionsupporting
confidence: 90%
“…13,48,79 Our mean hip anteversion values are within the range of normal values reported in healthy adults (7°-18°), as measured by both clinical and diagnostic methods. 8,36,63,65,71,72 Our findings of greater hip anteversion in females as compared to males agree with those of other studies 8,63 ; but the magnitude of the sex difference is much larger in the current study (approximately 9° versus 2°-4°). This disparity may be explained by differences in measurement methods, as the previous studies report measures on cadavers or with ultrasound and the current study used clinical measures in healthy subjects.…”
Section: Hip Anteversionsupporting
confidence: 90%
“…Our data for MatGrp 2 (mean SD, 14.1° 5.9°; range, 6°-30°) are in line with those reported for 13 to 16 year olds in 2 of these studies (means ranging from 8° to 20°), 21,82 and our values in MatGrp 3 (10.9° 5.0°; range, -2.2°-21°) appear to be consistent with those obtained in healthy adult males and females (means ranging from 7° to 18°) using both clinical and imaging measurement methods. 10,38,54,60,61,66,68 However, our values for MatGrp 1 are substantially lower than those reported elsewhere. 21,78,82 Although using 2 testers introduces the potential for systematic differences between testers, 71 each tester measured subjects in all maturation groups; so it is unlikely that systematic measurement error alone explains these disparate findings.…”
Section: Methodscontrasting
confidence: 82%
“…A study using CT to measure the transmalleolar axes of 504 adult tibiae found a discrepancy of 3.4˚ between right and left sides, with the right being the more external (Strecker et al 1997). Seber (2000) did not find any significant difference between left and right tibial torsion in 50 healthy male participants according to CT. Krishna et al (1991) Only those trials with a knee ab/adduction range of less than 16i ncluded. Pelvic protraction, internal hip rotation, external hindfoot-thigh angle, external transmalleolar axis, internal foot progression angle, and internal knee progression angle are positive.…”
Section: Discussionmentioning
confidence: 84%